Overview on the progress of the conceptual studies of a gamma ray spectrometer instrument for DEMO. (1st August 2022) - Giacomelli, L.; Nocente, M.; Perelli Cippo, E.; Rebai, M.; Rigamonti, D.; Tardocchi, M.; Cazzaniga, C.; Cecconello, M.; Conroy, S.; Hjalmarsson, A.; Ericsson, G.; Franke, T.; et al.
Abstract: The future DEMO tokamak will be equipped with a suite of diagnostics which will operate as sensors to monitor and control the position and operation parameters of DT plasmas. Among the suite of sensors, an integrated neutron and gamma-ray diagnostic system is also studied to verify its capability and performance in detecting possible DEMO plasma position variations and contribute to the feedback system in maintaining DEMO DT plasma in stable conditions. This work describes the progress of the conceptual study of the gamma-ray diagnostic for DEMO reactor performed during the first Work-Package contract 2015–2020. The reaction of interest for this Gamma-Ray Spectrometer Instrument (GRSI) consists of D(T, γ) 5 He with the emission of 16.63 MeV γ rays. Due to DEMO tokamak design constraints, the gamma and neutron diagnostics are integrated, both featuring multi-line of sight (camera type), viewing DEMO plasma radially with vertical (12) and horizontal (13) viewing lines to diagnose the γ and neutron emission from the DT plasma poloidal section. The GRSI design is based on the investigation of the reaction cross sections, on the calculations performed with GENESIS and MCNP simulation codes and on the physics and geometry constrains of the integrated instrument. GRSI features long collimators which diameters are constrained by the neutron flux at the neutron detectors of the Radial Neutron Camera (RNC) system placed in front, which are key to control DEMO DT plasma position. For these reasons, only few GRSI parameters can be independently selected to optimize its performance. Among these, the choice of the collimator diameters at the back side of the neutron detector box up to the GRSI detector, the use of LiH neutron attenuators in front of the GRSI detectors, the GRSI detector material and shielding. The GRSI detector is based on commercial LaBr3 (Ce) inorganic scintillating crystal coupled with a photomultiplier tube or a silicon photomultiplier. They are designed to operate at high count rate although GRSI geometry constraints severely impact on this feature. The GRSI can also provide an independent assessment of DEMO DT fusion power and T burning.